Clinical insights on severe dilated cardiomyopathy and atrial fibrillation in a young Pomeranian - Hermawan, Intan Permatasari; Palestin, Palestin (ARSHI Veterinary Letters, 2024)
Dilated cardiomyopathy (DCM) and atrial fibrillation are severe cardiac conditions in small-breed dogs that are often linked to carnitine and taurine deficiencies. This case study assesses the effectiveness of carnitine supplementation and a cardiac-specific diet in a 4-year-old, 3.8 kg Pomeranian named Boxy, who presented with symptoms including appetite loss, vomiting, exercise intolerance, and dyspnea. Initial diagnosis revealed severe heart enlargement (VHS 16.2V), right auricular bulging, tracheal collapse, and atrial fibrillation. Treatment with Cardi-B, Capritazine syrup, and Royal Canin cardiac diet significantly improved after 30 days, with normalised blood pressure (103/59 mmHg) and a reduced VHS of 13.7V. Echocardiography revealed no tamponade. Boxy remains on daily Cardi-B and Royal Canin Cardiac for ongoing evaluation until the heart size and ECG readings normalise